ADHERANCE TO BREAST AND CERVICAL CANCER SCREENING ENSURING COMPLIANCE WITH ETHICAL PRINCIPLES IN THE REPUBLIC OF KAZAKHSTAN - A. G. Shamsutdinova; B. S. Turdaliyeva; B. A. Ramazanova; A. G. Beltenova (Сибирский онкологический журнал)
The aim of the study was to assess adherence to breast and cervical cancer screening ensuring compliance with ethical principles.Material and methods. A total of 1,015 women of target age groups, living in Almaty, the Republic of Kazakhstan, participated in breast and cervical cancer screenings. A structured questionnaire was used to collect data from each participant (1,239 questionnaires: 674 for breast cancer screening and 565 for cervical cancer screening). Two hundred and twenty-four women participated in two screenings. The survey was conducted immediately after the respondents had had a mammography and / or Pap test. The questionnaire included the socio-demographic characteristics of women, questions on awareness of screening, level of knowledge before and after screening, sources of information, feelings before screening, after screening and and also after the receipt of test results. Binary logistic regression was used for data analysis.Results. Sixty-one percent (95 % CI 57.7; 63.1) of women participated in screening for the first time, 39 % (95 % CI 36.4; 41.8) of respondents visited outpatient clinic for the second and the third time. Multivariable analysis revealed that the participation in screening was associated with the purpose of visit, awareness and confidentiality. Thus, women, who arrived at the outpatient clinic with purposes other than screening were 2.3 times less (OR=2 95 % CI 1.6; 3.1) likely to participate in next screening compared to those, who came to the clinic with the purpose of screening as well as those, who were referred by employers (OR=2 95 % CI 1.2; 3.2) or friend/family (OR=2 95 % CI 1.0; 4.3). Women, who had little information about screening as a whole and about screening test before it was taken, were 3 and 2 times less likely to come to screening again (OR=3 95 % CI 1.6; 5.9 and OR=2 95 % CI 0.8; 3.7, respectively). The confidentiality violation led to a decrease in chance (OR=3.5 95 % CI 2.2; 4.9) of being screened again for those women, who experienced nervousness and shame during the screening, and also indicated the presence of nonmedical people during the test.Conclusion. Measures aimed to ensure compliance to ethics in screening for breast and cervical cancer will improve the quality of screening programs in accordance with international standards, as well as increase the personal responsibility for active participation in screening.